Factors influencing knowledge and behaviors related to food safety during purchasing among consumers in Libya (Journal of Patan Academy of Health Sciences, 2022)
Introduction: Libyan consumers mainly rely on purchasing food products and preparing them at home. Therefore, knowing the rules of food safety when purchasing is key to protect them from foodborne diseases. This study aims to assess food safety knowledge and behaviours during purchasing among consumers in Libya.Method: The study was carried out through the internet by Qsurvey and filling paper questionnaires by self-administration method to explore the level of food safety knowledge and practices during purchasing among consumers in Libya, from March to December 2020. Data were analyzed by SPSS. A Chi-square test was used to determine the influence of demographics on the level of knowledge and behaviours. Bivariate correlation coefficient analysis was used to determine the correlation between knowledge and behaviours scores. A p value of